Pajak, Transparansi, dan Tindak Pidana Ekonomi Lintas Negara: Implikasi Penggelapan Pajak bagi Kedaulatan Fiskal Negara Berkembang - Samudra, Awang; Purwati, Ani (SENTRI: Jurnal Riset Ilmiah, 2025)
Tax evasion, as a form of cross-border economic crime, has become increasingly complex in the era of globalization. Developing countries are the most disadvantaged, as multinational corporations exploit loopholes in international tax regulations and the lack of financial transparency. This article aims to examine the implications of tax evasion on the fiscal sovereignty of developing nations using a normative juridical approach and literature review. The discussion focuses on the importance of international cooperation, tax system reform, and the implementation of transparency principles as key measures to prevent transnational economic crimes. The findings indicate that, without comprehensive national regulatory reform and active participation in international tax agreements, developing countries will continue to suffer from significant revenue losses. Addressing these challenges requires coordinated efforts between governments, international organizations, and the private sector to build a more just and accountable global tax system that protects the fiscal interests of developing economies.